Mental illness as social product or social construct: a contradiction in feminists’ arguments? - Busfield, Joan (Sociology of Health & Illness, 2008)
Feminists have been taken to task for suggesting both that the higher level of mental illness observed in women is a consequence of the oppression they face - an oppression which drives them into madness and mental disorder - and also that the concept of mental illness is a social construct inappropriately and incorrectly applied to women by a patriarchal order as a means of social control. This paper examines this supposed contradiction and the ideas that underly the contrasting contentions. It argues that the two positions are not in fact incompatible.
Number: 4
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; angleterre; approches et analyses; cours; discipline; europe; inégalités; patriarcat; premier cycle; périodes historiques; régions géographiques; santé; santé mentale; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques; états-unis

Intersex: a perilous difference - Holmes, Morgan (Susquehanna University Press, 2008)
As threatening evidence that sex is not the natural basis upon which oppositional gender roles are built, the intersexed are made to disappear into normative categories, thus aligning once again the rightful place of male and female as opposites.
Keywords: LGBTQIA2+; approches et analyses; corps; cours; discipline; intersexuation; patriarcat; personnes intersexes; premier cycle; santé; sciences humaines; soc2014; sociologie; système médical; systèmes d'oppressions; thématiques; violences; violences médicales